Peranan sorbitol dalam mempertahankan kestabilan pH saliva pada proses pencegahan karies (The role of sorbitol in maintaining saliva’s pH to prevent caries process) - Diana Soesilo; Rinna Erlyawati Santoso; Indeswati Diyatri (Dental Journal (Majalah Kedokteran Gigi), 2005)
People in Indonesia often consume food containing sucrose. If the sucrose consumed is in a large amount, it will decrease saliva’s pH and soon teeth destruction will happen. To avoid it, it is necessary to change sucrose consumption habit into another kind of sugar, namely sorbitol. Sorbitol is preferred to use, because it is cheaper and easier to get. Sorbitol is made from cassava, which is plentifully grown in Indonesia. Sorbitol is not good media for bacteria to grow. Because sorbitol has a diol, so it’s difficult to catalyst by glucosyltransferase enzyme, which is produced by bacteria Streptococcus mutans. The conclusion is that sorbitol is difficult to be fermented by Streptococcus mutans so it will not decrease saliva’s pH.